Research on the stability of building mixture structure/Statybinių mišinių struktūros tyrimas - Deltuva, Juozas (Journal of Civil Engineering and Management, 2001)
The aim of this work is to establish the system of quantities that would be suitable to evaluate the stability of the structure of concrete in order to assure that the structure of mixtures and building articles is uniform during the given production period. Concrete is a polystructured material and therefore its structure must be analyzed at all levels. According to concept of the materials science, the spatial structure of such a material is defined by the arrangement and interconnections of component particles or component blocks that can be considered as discrete structural elements. A structural element is the smallest cell of material that contains all the material ingredients at the same proportions as the entire volume. A structural element is formed by a large particle of medium size and the interface layer is of small particles and liquid components. The presented method may be applied when it is desirable to compute, compare or model the structures of concrete and other building mixtures and calculate the structural uniformity indices. According to given uniformity of macro structure, it is possible to determine by the use of structural elements the admissible aggregate grain-size tolerances, in order to achieve the uniform structure, the strength and deformability. The reliability of the uniformity of a concrete structure must be regulated according to its type and function; it is especially important for load bearing reinforced concrete where a real deformation of concrete must conform to the calculated allowable one.Article in Lithuanian.First Published Online: 30 Jul 2012